FILSAFAT PENDIDIDIKAN ESENSIALISME DAN PERENIALISME - Rosyidan, Yasir (AL-MUTSLA, 2024)
Abstract The philosophy known as essentialism advocates a return of humanity to ancient civilizations. According to their beliefs, humanity has benefited greatly from ancient culture. The Essentialist school of thought prioritizes not abandoning cultures that have survived for a long time. Essentialism and permanence have similar properties. During the 13th century AD, perennialism proudly recognized the success of the ideas and thoughts of ancient civilizations, including Greece and the Middle Ages. They believe that the ideas and concepts of these two eras are still valuable today. This approach uses a qualitative methodology, which involves the use of a 'literature research model that analyzes content from multiple sources and combines references. This study seeks to investigate the philosophical stance of essentialism and perennialism in relation to education. Keywords: Philosophy, Essentialism and Perenialism.